Educação científica em foco : concepções de professores da Rede Estadual da Bahia que atuam no Programa Ciência na Escola - Silva, Henrique Cardoso (2018)
The objective of this study was to analyze the conceptions about the Scientific Education of the professors that develop scientific research activities in the Science in the School Program (PCE), in the state schools of Catu, between the years of 2013 and 2016. The research consists of a qualitative case study, making use of the methodology of data collection adapted, based on the proposal of Hewson and Hewson (1988) denominated CTSI - Conception of Teaching Science Interview, through semi-structured interview. Data analysis was done through the Discursive Textual Analysis Technique (MORAES, 2003; MORAES; GALIAZZI, 2005). As a result, it was observed that the understandings were constructed through ten emerging categories: "Research as a foundation for the (re) construction of knowledge", "Reconstructive questioning as a fomenting citizen performance", "The activity of orientation as an attitude "The teacher as he organizes the mobilization of young researchers", "The protagonism as the impeller of the students' epistemic positioning", "Decision-making as an attitude of criticism and reflection", "Scientific education as a innovative modality capable of (re) signifying teaching and student performance "," Scientific Education as a strategy to promote the student's epistemic posture "," Scientific education and its contribution to the social function of science teaching from a citizen perspective "and "Scientific education as" glasses "for overcoming distancing and the teaching of science and everyday life. " These categories indicate adherence to the main theorists who discuss the Scientific Education, thus not presenting significant deformations that compromise the vision about this modality of education.